OUTCOME OF DISTALLY BASED SURAL ARTERY FLAP FOR DISTAL THIRD OF LEG AND FOOT DEFECTS - Singh, Kuldeep; Rohilla, Rajesh; Singh, Raj; Singh, Sarita; Singh, Bikramjit; Tanwar, Milind (Journal of Ayub Medical College Abbottabad, 2017)
Background: Due to precarious blood supply, skin coverage for defects of leg, heel, dorsum of foot and the ankle has been a complicated task for plastic surgeons & orthopaedic surgeons. The present study aimed to prospectively evaluate the outcome of distally based sural flap for coverage of defects distal third of leg, ankle & foot. Method: In this study 15 patients with soft tissue defects on distal third of leg in (n=2), heel (n=4), medial malleolus (n=3), lateral malleolus (n=1), Achillis tendon (n=2), anterior ankle (n=2) and in dorsum of foot (n=1) were operated for coverage of defect by distally based sural flap. All the cases were done as secondary procedures. Results: All the flaps showed good results except five minor complications. Three flaps showed superficial skin necrosis and two showed partial tip necrosis. Conclusions: Distally based sural artery flap is very useful in covering the defects of lower leg, heel and dorsum of foot. It is reliable, easy to raise with minimal morbidity to the patient. This flap does not sacrifice any of the major vessels of the limb and hence it is very safe flap. Keywords: sural artery flap; distal third leg; dorsolateral foot defect; posterior heel defect